The Influence of Leadership Transformational Style on Employee Work Productivity and Its Implications on The Performance and Health Level of The People's Economy Bank - Akhsan Okta Hidayat; Cecep Taofiqurrochman (Advances In Social Humanities Research, 2026)
Employee engagement is essential for sustaining organizational performance in banking institutions that depend on service quality, integrity, professionalism, and coordinated employee behavior. This study aimed to examine the effects of corporate culture and transformational leadership on employee engagement at YKP Bank Bjb. A quantitative explanatory research design was applied to all 24 employees using a census sampling technique. Data were collected through a five-point Likert-scale questionnaire and analyzed using structural equation modeling–partial least squares (SEM–PLS) with SmartPLS 4, including descriptive analysis, measurement model assessment, structural model evaluation, and hypothesis testing. The findings showed that all constructs achieved adequate validity and reliability, with outer loadings ranging from 0.721 to 0.918 and average variance extracted (AVE) values exceeding 0.50. Corporate culture had a positive and significant effect on employee engagement (t = 5.140; p < 0.001), while transformational leadership also had a positive and significant effect on employee engagement (t = 3.186; p = 0.001). Together, both variables explained 97.8% of the variance in employee engagement. These findings indicate that organizational values and transformational leadership behaviors complement each other in strengthening employees’ enthusiasm, organizational attachment, and involvement. The study concludes that employee engagement can be enhanced through the reinforcement of service excellence, integrity, professionalism, inspirational motivation, intellectual stimulation, and individualized consideration.